Research on Resolution Enhancement Technology of Orthogonal Multimode Fiber Imaging. Issue 1 (1st April 2022) - Wang, Xinyi; Yin, Longfei; Wu, Guohua; Luo, Bin; Yin, Pengqi
Abstract: This paper presents a new scheme to improve the imaging resolution of optical fiber endoscope. Multimode fiber imaging is combined with correlation imaging experimental architecture, and Schmidt orthogonalization algorithm is used to reduce the correlation of light field. The simulation and experimental results show that this scheme can greatly improve the imaging quality and resolution, especially in the case of under sampling. In addition, the scheme can also resist the low resolution problem caused by the light field divergence of multimode fiber correlation imaging, and when the light field divergence reaches a certain extent, the resolution of the orthogonalized multimode fiber light field will no longer be affected. The feasibility of orthogonal multimode fiber imaging scheme in large depth of field is verified.